Diagnostic accuracy of 4D-MRA for the detection and localization of spinal dural arteriovenous fistulas: A retrospective 10-year cohort study - Frederick J.A. Meijer; Vincent Raymaekers; Sjoert A.H. Pegge; Jeroen HD. Boogaarts (Brain and Spine)
Research question: The goal of this study was to assess the diagnostic accuracy of spinal time-resolved contrast-enhanced MR angiography (4D-MRA) for the detection and localization of spinal dural arteriovenous fistulas (SDAVF) in our institution. Material and methods: Single center retrospective cohort study of patients with the clinical suspicion of a SDAVF. Patients were included who had undergone spinal 4D-MRA in the period January 2010–February 2021. A subgroup was identified, who had subsequent digital subtraction angiography (DSA), or clinical/radiological follow-up. Diagnostic performance measures of 4D-MRA were calculated (sensitivity, positive predictive value, specificity, and negative predictive value) with DSA serving as the reference standard. Results: Overall, 120 patients with the clinical suspicion of having a SDAVF and who underwent spinal 4D-MRA were identified. A subgroup of 30 patients had both 4D-MRA and DSA, or follow-up. In this group, the sensitivity of 4D-MRA for the detection of a SDAVF was 100% and specificity was 91% (positive predictive value of 95% and a negative predictive value of 100%). Sidedness was correctly identified on 4D-MRA in 74% of the cases and the level of the SDAVF in 68%. Discussion and conclusion: The results indicate that 4D-MRA has a high sensitivity and specificity for the detection and localization of a SDAVF, which is in line with previous studies published in literature. Furthermore, 4D-MRA can serve to guide DSA and shorten the procedural time, which reduces the risk of angiography related complications, and decreases patient discomfort.